EDUPRENEURSHIP 5.0: KULINER TASIKMALAYA UNTUK GENERASI DIGITAL - Eva Alawiah; Risbon Sianturi; Irma Siti Anisa; Nizza Nadya Rachmani; Elsakira, Lena (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study discusses the concept of "Edupreneurship 5.0" in the context of the culinary industry in Tasikmalaya, West Java, which faces challenges and opportunities in the era of Industry 4.0 and Society 5.0. Edupreneurship 5.0 integrates advanced technologies, such as artificial intelligence and the Internet of Things (IoT), with entrepreneurship education to shape a generation of young people who are innovative and adaptable to the developments of the global market. Using a descriptive qualitative approach and a case study of the TO Mughni rice business, this research collects data through interviews and documentation to analyze the business background, capital, profits, employee management, and marketing strategies. The findings show that the entrepreneur has been able to survive and grow in a competitive environment by implementing efficient management strategies and utilizing digital platforms for marketing. The concept of Edupreneurship 5.0 is expected to facilitate the digital generation in developing technology-based culinary businesses, preserving local wisdom, and creating business models that are adaptive to the changing times. This article discusses "Edupreneurship 5.0: Tasikmalaya Culinary for the Digital Generation."